Предмет: Математика,
автор: енот328
3⁻⁵:3⁻⁷-2⁻²*2⁴+((²₋₃)⁻¹)³
Ответы
Автор ответа:
0
3⁻⁵:3⁻⁷-2⁻²*2⁴ = 3² - 2² = 9 - 4 = 5
((2/3)⁻¹)³ = (3/2)³ = 27/8
5 + 27/8 = 40/8 + 27/8 = 67/8 = 8 3/8
((²₋₃)⁻¹)³ - вот это я не поняла, что вы хотели написать?
((2/3)⁻¹)³ = (3/2)³ = 27/8
5 + 27/8 = 40/8 + 27/8 = 67/8 = 8 3/8
((²₋₃)⁻¹)³ - вот это я не поняла, что вы хотели написать?
Автор ответа:
0
две третьи
Автор ответа:
0
Проверяйте
Похожие вопросы
Предмет: Химия,
автор: ksenaboyko1012
Предмет: Қазақ тiлi,
автор: asslkhan005
Предмет: История,
автор: katakuznecik870
Предмет: Алгебра,
автор: keenneenenene
Предмет: Математика,
автор: madinaru46